Studying pollen representation of vegetation and plant richness from Pampean coastal dunes (Argentina, South America): exploring from local to landscape quantitative linkages - Carolina Vásquez; Gonzalo Sottile; Victor Merino-Campos; Silvina Stutz (Boletín de la Sociedad Argentina de Botánica)
Background and aims: Studying plant dynamics through past pollen records may contribute to a better understanding of long-term changes in plant communities. Thus, this study aims to establish whether surface pollen composition and richness of the Argentinean Coastal Dune System reflect landscape heterogeneity in coastal dune environments.